2018
DOI: 10.2174/1389203718666170829162335
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II: Molecular Mechanisms of Biological Activity

Abstract: Urotensin II (UT II) is an important factor of cellular homeostasis. This regulatory peptide is involved in the pathophysiology of many disorders. For example, it plays an important role in the pathogenesis of acute and chronic diseases, stressful and adaptive reactions of the body, in the development of cardiovascular pathologies, metabolic syndrome, inflammation, liver cirrhosis, renal failure, diabetic nephropathy, reproductive dysfunction, progression of psychosomatic, psychoendocrinal and psychiatric diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was shown that serum UII levels are elevated in conditions such as heart failure, renal failure, liver disease and diabetes [ 31 ]. According to the review by Svistunov et al, UII is involved in the pathophysiology of many stressful and adaptive reactions and in the development of cardiovascular pathologies [ 32 ]. It also appears that its role in biomedicine is not completely clear as a recent animal study showed that the deletion of the UTR in knockout mice does not affect basal hemodynamics in comparison to wild-type mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that serum UII levels are elevated in conditions such as heart failure, renal failure, liver disease and diabetes [ 31 ]. According to the review by Svistunov et al, UII is involved in the pathophysiology of many stressful and adaptive reactions and in the development of cardiovascular pathologies [ 32 ]. It also appears that its role in biomedicine is not completely clear as a recent animal study showed that the deletion of the UTR in knockout mice does not affect basal hemodynamics in comparison to wild-type mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…U-II is a peptide ligand that acts as a potent vasoconstrictor, which was originally discovered four decades ago. The vasoconstriction activity of U-II is 10-fold more potent than that of endothelin-1[ 6 ]. Most studies of U-II have been conducted to understand its role in the development of cardiovascular diseases[ 7 ].…”
Section: To the Editormentioning
confidence: 99%
“…A major cellular homeostasis component, urotensin II (UII) contributes to the development of both acute and chronic diseases, inflammation, liver cirrhosis, and other conditions (138). It has been determined to affect angiogenesis and mitogenesis, using its receptor (UII-R) to exert a potent angiogenic effect in vivo as well as in vitro (139).…”
Section: The Effect Of Urotensin II (Uii) In the Common Types Of Cancermentioning
confidence: 99%